Natural compounds modulate the autophagy with potential implication of stroke - Anil Ahsan; Mengru Liu; Yanrong Zheng; Wenping Yan; Lin Pan; Yue Li; Shijia Ma; Xingxian Zhang; Ming Cao; Zhanxun Wu; Weiwei Hu; Zhong Chen; et al. (Elsevier, 2021)
Stroke is considered a leading cause of mortality and neurological disability, which puts a huge burden on individuals and the community. To date, effective therapy for stroke has been limited by its complex pathological mechanisms. Autophagy refers to an intracellular degrading process with the involvement of lysosomes. Autophagy plays a critical role in maintaining the homeostasis and survival of cells by eliminating damaged or non-essential cellular constituents. Increasing evidence support that autophagy protects neuronal cells from ischemic injury. However, under certain circumstances, autophagy activation induces cell death and aggravates ischemic brain injury. Diverse naturally derived compounds have been found to modulate autophagy and exert neuroprotection against stroke. In the present work, we have reviewed recent advances in naturally derived compounds that regulate autophagy and discussed their potential application in stroke treatment.